2017
DOI: 10.18632/oncotarget.15579
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial microparticles delivering microRNA-155 into T lymphocytes are involved in the initiation of acute graft-versus-host disease following allogeneic hematopoietic stem cell transplantation

Abstract: Endothelial microparticles (EMPs) upregulation has been observed in acute graft-versus-host disease (aGVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the role of EMPs remains unclear. We found that EMPs derived from TNF-α-stimulated human umbilical vein endothelial cells (EA.hy926) concentrated more microRNA-155 (miR-155) compared with maternal cells. The miR-155 levels in MPs from peripheral blood of aGVHD patients and mice were remarkably elevated and significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…This finding, combined with the observation that EMVs bind with CD4+ and CD8+ T cells, may provide another explanation on how EMVs modulate immune response. Other observations support the view that EMVs act as activators of T cells response (159, 160). The number of Th1 cells increased when peripheral blood mononuclear cells were co-incubated with EMVs (159).…”
Section: Endothelial-derived Microvesicles (Emvs) and Inflammationsupporting
confidence: 74%
See 1 more Smart Citation
“…This finding, combined with the observation that EMVs bind with CD4+ and CD8+ T cells, may provide another explanation on how EMVs modulate immune response. Other observations support the view that EMVs act as activators of T cells response (159, 160). The number of Th1 cells increased when peripheral blood mononuclear cells were co-incubated with EMVs (159).…”
Section: Endothelial-derived Microvesicles (Emvs) and Inflammationsupporting
confidence: 74%
“…Thus, it may be speculated that EMVs use T-bet to promote Th1 cell differentiation and cytokine synthesis. Subsequent research demonstrated that EMVs deliver miR-155 to T cells (160). Although encapsulated miR-155 does not influence proliferation and apoptosis of T cells, miR-155 inhibition causes suppression of IFN-γ, IL-2, IL-9, and IL-17A release, while increasing the release of other cytokines such as IL-4, IL-6, and IL-10 (160).…”
Section: Endothelial-derived Microvesicles (Emvs) and Inflammationmentioning
confidence: 99%
“…PBMCs were isolated from mouse peripheral blood samples using the standard Ficoll-Hypaque density gradient centrifugation methods as previously indicated [ 61 , 62 ]. In brief, T lymphocytes were prepared from mouse PBMCs by negative selection with magnetic bead depletion of non-T lymphocytes with the EasySep mouse T lymphocytes isolation kit (Stemcell Technologies, USA) according to the instructions provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the dysregulation of miR155 in mouse model drives T H 1 proinflammatory T-cell phenotype (84). In this context, the infusion of EVs loaded with anti-miR155 in preclinical models reduced differentiation toward T H 1, T H 9, and T H 17 cells and skewed differentiation toward T H 2 and Treg cells, thus ameliorating the manifestations of GvHD and increasing mice survival (85).…”
Section: Ev Applications In Gvhdmentioning
confidence: 99%